BLOOD CHOLESTEROL, LDL AND HDL IN CROSSBRED LOCAL CHICKEN FEED INULIN OF DAHLIA TUBERS AS A PREBIOTIC - Nurul Fajrih (Chalaza Journal of Animal Husbandry, 2016)
The feeding inulin of dahlia tubers as a prebiotic related to the quality of the resulting product is a product low cholesterol. The research was aimed to examine the role of inulin as a prebiotic derived from dahlia flower tuber in the form of powder and extract on blood cholesterol, low density lipoprotein (LDL) and high density lipoprotein (HDL) of crossbred local chicken. The research was assigned in a completely randomized design with 7 treatments and 4 replications (10 birds each), treatments applied were T0: basal ration, T1: ration + 0.4% powder of dahlia tuber, T2: ration + 0.8% powder of dahlia tuber, T3: ration + 1.2% powder of dahlia tuber, T4: ration + 0.39% extract of dahlia tuber, T5: ration + 0.78% extract of dahlia tuber, T6: ration + 1.17% extract of dahlia tuber. The birds were reared for conditioning from day 1 until 3 week, and dietary treatment was given thereafter until 11 week of age. Parameters observed were blood cholesterol, LDL and HDL. The data were statistically analyzed according to ANOVA and continued to Duncan test at the level of 5% probability. The results showed that feeding inulin in the form of powder or extract significantly (P0,05) decreased LDL and HDL, but not on blood cholesterol. In conclusion, feeding inulin in the form of powder in 1.2% (T3) and extract in 1.17% (T6), able to reduce levels of LDL and HDL but not yet capable of lowering blood cholesterol of crossbred local chicken.